The effects of parturition season and suckling mode on the puerperium of santa ines ewes and on the weight gain of lambs - Oliveira, M. E F [UNESP]; Sousa, H. L L; Moura, A. C B; Vicente, W. R R [UNESP]; Rodrigues, L. F S; Araújo, A. A. (FapUNIFESP (SciELO), 2013)
Seventy-seven ewes were randomly divided into groups according to parturition season and suckling mode [Rainy season: continuous (n=14) and controlled (n=13); Dry season: continuous (n=25) and controlled (n=25)]. The controlled suckling mode, in both seasons, resulted in a decrease in variables, intervals between parturition and first estrus (reduction of 27.11 and 11.46 days for rainy and dry season, respectively; P<0.05) and between parturition and estrus of conception (reduction of 12.81 and 13.58 days, for rainy and dry season, respectively; P<0.05). As to the lambs, the weight gain was higher in animals subjected to controlled suckling in relation to continuous, especially when lambing occurred in the rainy season (17.83±0.56 vs. 13.95±0.52kg for Lambs' weight at 90 days old, respectively; P<0.05). Therefore, it was concluded that controlled suckling management is better indicated for the Amazonian region, since it allows the ewes to have a shorter puerperium period and the lambs exhibit higher weight gain.
Keywords: Puerperium; Sheep; Suckling; Weight gain